Ответы и объяснения

Лучший Ответ!
2013-02-08T12:45:51+00:00

Все во вложении

*********************************************************************

 

2013-02-08T12:51:27+00:00

1)  -2x^2 + 3x + 5 = 0

D = 9+40 = 49

x1 = (-3+7)/(-4) = -1

x1 = (-3-7)/(-4) = 2,5

 

-2x^2 - x +1 = 0

D = 1 + 8 = 9

x1= (1+3) / (-4) = -1

x1 = (1-3) / (-4) = 0,25

 

(5 + 3x - 2x^2) / ( 1-x-2x^2) = ((x+1)(x-2,5)) / ((x+1)(x-0,25)) = (x-2,5) / (x-0.25_

 

 2) 3x^2-4x-4 = 0

D = 16 + 48 = 64

x1=(4+8)/6 = 2

x2=(4-8)/6=-2/3

 

-x^2-x+6=0

D=1+24=25

x1=(1-5)/(-2)=2

x2=(1+5)(-2)=-3

 

 

(3x^2-4x-4)/(6-x-x^2) = ((x+2/3)(x-2)) / ((x-2)(x+3)) = (x+2/3) / (x+3)